The Influence of Augmented Reality (Ar) Media on The Learning Outcomes of SMP Negeri 2 Woha Students in Ict Subjects - Julkifli, Fahrul; Hardiansyah, Hardiansyah; Hakim, Arif Rahman (Journal of Educational Sciences, 2025)
The advancement of digital technology in education demands innovative approaches that not only assess learning outcomes but also enhance students' motivation. At the junior high school level, ICT subjects are often perceived as challenging, with many students performing below the minimum standard, particularly in practical skills, and showing low interest in conventional methods. This study aimed to investigate the effect of Augmented Reality (AR) media on students' learning outcomes and motivation in ICT at SMP Negeri 2 Woha. A quantitative approach with a quasi-experimental Non-Equivalent Control Group Design was applied, involving two classes of 30 students each. The experimental class received learning with AR media, while the control class continued with conventional methods. Data were collected through pretests, posttests, questionnaires, and observations, then analyzed using SPSS and JAMOVI. The findings showed that the experimental class achieved an average posttest score of 85.4 with a medium N-Gain of 0.54, while the control class only reached 75.2 with a low N-Gain of 0.22. Moreover, motivation in the AR class was higher (average 4.38) than in the control class (3.15). In conclusion, AR media effectively supported ICT learning and can serve as an innovative tool for fostering 21st-century skills.